SISTEM PENJUALAN PADA TOKO SAMUDRA BARU BERBASIS WEB - Ti, Jemmy (LPPM Universitas Putera Batam, 2021)
Technology is one of the fastest growing field in the world. A lot of business sectors have started implementing technology into their business part. One of them is store building. As a store grows, they will have more transactions everyday and that means more transactions will need to be noted down manually by the workers. However, as the transaction amount grows this method is not efficient and recommended because it is slow and there are chances of human errors which will cause loses to the store. The aim of this study is to create an application that will keep track of all the transactions made in the store and help the store owner to keep track of the transactions done by the store workers as well as minimize the store losses caused by employee mistakes. The method used will be by creating a web based application, this application will be made using ASP.NET and C# as the programming language and Microsoft SQL Server for database. From the observation that are done, the created application made it easier for the owner to keep track of the transactions done by the workers and made the accounting calculation faster and easier.